UNB hockey conference "Skating into the future: Hockey in the new millenium " (2004)
Abstracts der Vorträge, die auf der Tagung gehalten wurden, u.a.: PERSONALITY CHARACTERISTICS OF OFFICIALS IN CONTACT, NON-CONTACT AND INDIVIDUAL SPORTS Balch, M., Leavins,N., & Scott, D., CORRELATIONS BETWEEN HOCKEY SKATING PERFORMANCE AND PHYSIOLOGICAL MEASURES. Behm DG, Wahl M, Button D, Power K. DETERMINING THE PRECISION AND ACCURACY OF AN ON-ICE SKATING TEST TO PREDICT MAXIMAL OXYGEN CAPACITY Faught, B.E., M. Nystrom,. W.J. Montelpare, and K.L. Lockwood. PHYSIOLOGICAL TESTING OF A MENS VARSITY HOCKEY TEAM: A FIVE-YEAR ANALYSIS Fowles, J.R., R.J.L. Murphy, D.L. Kruisselbrink, and G.D. Ness. THE NEXT SEASON: IMPACT OF THE HOCKEY HEART STUDY ON ADULT RECREATIONAL HOCKEY PLAYERS M.F. Harrison; J.R. Sexsmith; WHAT DO VARSITY HOCKEY PLAYERS REALLY SKATE ON? K.L. Lockwood & A.J. Winchester PSYCHOLOGICAL CHARACTERISTICS OF ELITE HOCKEY PLAYERS Mike MacDougall, Nena Levins, Kendall Sommers, and David Scott GAZE BEHAVIOUR AND DECISION-MAKING OF CANADIAN NATIONAL TEAM ICE HOCKEY PLAYERS. S. T. Martell, J. N. Vickers ( A BIOMECHANICAL COMPARISON OF SKATING TECHINIQUE IN DEVELOPMENTAL AND ELITE ICE HOCKEY PLAYERS M. McPherson, W. Montelpare, A. Wrigley, N. Purves, J. McAuliffe, T. Socha THE INTEGRATION OF PHYSIOLOGICAL AND PSYCHOLOGICAL DEVELOPMENT PROGRAMS ON THE ACQUISITION OF POWER IN ELITE ICE-HOCKEY PLAYERS. J. Patrick Neary, Howard A. Wenger, Cal B. Botterill THE EFFECTIVENESS OF AN OFF-ICE HOCKEY SKATING SIMULATOR TO IMPROVE LEG POWER AND ON-ICE SPRINT PERFORMANCE M.Price, J. R. Fowles and G. Sleivert